Exploration of Pathogenesis and Cutting-Edge Treatment Strategies of Sarcopenia: A Narrative Review - Gao Y; Liu D; Xiao Q; Huang S; Li L; Xie B; Zhou L; Qi Y; Liu Y (Clinical Interventions in Aging)
Yin Gao,1,2,* Di Liu,1,2,* Qixian Xiao,1,* Shan Huang,1,2 Li Li,2 Baocheng Xie,3 Limin Zhou,3 Yi Qi,2 Yanzhi Liu1 1Key Laboratory of Traditional Chinese Medicine for the Prevention and Treatment of Infectious Diseases, Institute of Clinical Medicine, Zhanjiang Central Hospital, Guangdong Medical University, Zhanjiang, 524037, People’s Republic of China; 2Marine Medical Research Institute of Zhanjiang, School of Ocean and Tropical Medicine, Guangdong Medical University, Zhanjiang, 524023, People’s Republic of China; 3Department of Pharmacy, The Tenth Affiliated Hospital of Southern Medical University (Dongguan People’s Hospital), Dongguan, 52305, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanzhi Liu, Email liuyanzhi@gdmu.edu.cn Yi Qi, Email qiyi7272@gdmu.edu.cnAbstract: Sarcopenia a progressive and multifactorial musculoskeletal syndrome characterized by loss of muscle mass and function, poses a significant global health challenge, particularly in aging populations. Epidemiological studies reveal that sarcopenia affects approximately 5– 10% of the general population, with prevalence rates escalating dramatically after age 60 to reach 10– 27% in older adults. This age-associated increase contributes significantly to healthcare burdens by elevating risks of disability, frailty, and mortality. Despite its profound impact, current clinical approaches to sarcopenia remain limited. While resistance exercise and protein supplementation form the cornerstone of management, their efficacy is often constrained by poor long-term adherence and variable individual responses, highlighting the urgent need for more comprehensive and personalized treatment strategies. The pathogenesis of sarcopenia is complex and influenced by various factors, including aging, inflammation, nutritional deficits, physical inactivity, and mitochondrial dysfunction. However, the precise molecular mechanisms underlying this condition are still not fully understood. Recent research has made significant strides in elucidating the intricate mechanisms contributing to sarcopenia, revealing novel insights into its molecular and cellular underpinnings. Notably, emerging evidence points to the pivotal role of mitochondrial dysfunction, altered myokine profiles, and neuromuscular junction degeneration in sarcopenia progression. Additionally, breakthroughs in stem cell therapy, exosome-based treatments, and precision nutrition offer promising avenues for clinical intervention. This review aims to synthesize the latest advancements in sarcopenia research, focusing on the novel contributions to its pathogenesis and treatment strategies. We explore emerging trends such as the role of cellular senescence, epigenetic regulation, and targeted therapeutic interventions that could reshape future approaches to managing sarcopenia. By highlighting recent breakthroughs and cutting-edge research, we hope to advance the understanding of sarcopenia and foster the translation of these findings into effective clinical therapies.Keywords: sarcopenia, muscle, aging, skeleton